(untitled) (Vietnam Journal of Community Medicine, 2026)
High burden of ventilator associated pneumonia (VAP) in Intensive Care Units results from multidrug resistance of pathogens. Objectives: To identify common pathogens as well as their antibiograms to building empiric therapy for VAP. Methods: A cross-sectional survey was carried out pathogens of VAP, diagnosed VAP according to CDC criteria, in Intensive Care Center at National Hospital for Tropical Diseases from 5/2023 – 4/2025. Results: There were 90 patients included with mean age of 68.7 ± 15,3 years, 83.0% was male, 60.0% having at least one comorbidity. Most common indications for invasive mechanical ventilation were pneumonia, sepsis and septic shock. Gram negative bacteria accounted for 99% VAP pathogens. Acinetobacter spp. was the most common pathogen accounted for 58.2%, Klebsiella spp. 19,4% and P. aeruginosa 14,6% with carbapenem resistance accounted for 100%, 85.0% and 80.0%, respectively. Especially, there was one strain of Klebsiella spp and one isolated P. aeruginosa showed resistant to colistin. Conclusions: The most prominent pathogens of VAP were Acinetobacter spp., Klebsiella spp. and P. aeruginosa with high ratio of carbapenem resistance and serious risk alarm with appearance of colistin resistance.